The interval between concussions does not influence time to asymptomatic or return to play: a CARE consortium study - Shumski, E. J.; Eagle, S. R.; Kontos, A. P.; Bazarian, J. J.; Caccese, J. B.; Chrisman, S. P. D.; Clugston, J. R.; McAllister, T. W.; McCrea, M.; Broglio, S. P.; Lynall, R. C.; Schmidt, J. D.; et al. (Sports Medicine, 2024)
Introduction: The purpose of this study was to determine if the time interval between two concussive events influences the number of days to asymptomatic status, days to return to play, or performance on common post-concussion assessments following the second concussion. Methods: Data from 448 collegiate athletes and service academy cadets with two concussions (time between concussions: median 295.0 days [interquartile range: 125.0-438.2]), 40.0% female) were analyzed from Concussion Assessment Research and Education (CARE) Consortium institutions between 2014 and 2020. Days between concussions was the primary predictor variable. Primary outcome measures included time to asymptomatic and time to return to play following the second concussion. Secondary outcome measures included total number of symptoms, total symptom severity, Balance Error Scoring System total score, and Standardized Assessment of Concussion total score within 48 h of their second concussion. Results: Time between concussions did not significantly contribute to the multivariate time to asymptomatic (p = 0.390), time to return to play (p = 0.859), or the secondary outcomes (p-range = 0.165-0.477) models. Time to asymptomatic (p = 0.619) or return to play (p = 0.524) did not differ between same-season and different-season concussions. Sex significantly contributed to the return to play (p = 0.005) multivariate model. Delayed symptom onset and immediate removal from play/competition significantly contributed to the total number of symptoms (p = 0.001, p = 0.014) and symptom severity (p = 0.011, p = 0.022) multivariate models. Conclusion: These results suggest that in a population with a large period between injuries, the time between concussions may not be relevant to clinical recovery.